2020
DOI: 10.1002/bies.202000180
|View full text |Cite
|
Sign up to set email alerts
|

Paneth cells: Maintaining dynamic microbiome‐host homeostasis, protecting against inflammation and cancer

Abstract: The human intestines are constantly under the influence of numerous pathological factors: enteropathogenic microorganisms, food antigens, physico‐chemical stress associated with digestion and bacterial metabolism, therefore it must be provided with a system of protection against adverse impact. Recent studies have shown that Paneth cells play a crucial role in maintaining homeostasis of the small intestines. Paneth cells perform many vital functions aimed at maintaining a homeostatic balance between normal mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 76 publications
(208 reference statements)
0
4
0
Order By: Relevance
“…This indicates increased synthesis and secretion of acidic luminal mucin by duodenal goblet cells [ 11 , 12 ]. The major goblet cell mucins in the small intestine are mucin 2 proteins, gel-forming secretory mucins that facilitate hydrolysis and absorption of nutrients [ 18 , 41 , 42 , 43 ]. In addition to serving as a protective intestinal epithelial barrier, this mucin (mucin 2) also functions as a habitat that supports probiotic populations and promotes epithelial cell function [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…This indicates increased synthesis and secretion of acidic luminal mucin by duodenal goblet cells [ 11 , 12 ]. The major goblet cell mucins in the small intestine are mucin 2 proteins, gel-forming secretory mucins that facilitate hydrolysis and absorption of nutrients [ 18 , 41 , 42 , 43 ]. In addition to serving as a protective intestinal epithelial barrier, this mucin (mucin 2) also functions as a habitat that supports probiotic populations and promotes epithelial cell function [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…49 Accordantly, the PCs respond to changes in microbial composition by secreting different factors, which form a protective biochemical barrier from adhesion, hyperproliferation and translocation of the intestinal microbial population. 50 Studies have reported that (i) the PCs number increased with the bacterial insemination's growth in the small intestine, and (ii) PCs are found throughout the colon in inflammatory condition, where they are usually absent. 51 The PCs' granules are formed by various antibacterial proteins: lysozyme, α-defensins (HD5 and HD6), secretory phospholipase A2 (sPLA2), and angiogenin-4 (Ang4).…”
Section: The Cells Of the Intestinal Epithelial Barrier (Ieb)mentioning
confidence: 99%
“…These cells can release different molecules, including antimicrobials, to control and modulate gut microbial communities 49 . Accordantly, the PCs respond to changes in microbial composition by secreting different factors, which form a protective biochemical barrier from adhesion, hyperproliferation and translocation of the intestinal microbial population 50 . Studies have reported that (i) the PCs number increased with the bacterial insemination's growth in the small intestine, and (ii) PCs are found throughout the colon in inflammatory condition, where they are usually absent 51 .…”
Section: Er Stress In Ibdmentioning
confidence: 99%
“…Paneth cells are important because they synthesize and secrete antimicrobial peptides in the small intestine, and their dysfunction may increase susceptibility to infection [ 13 ]. Paneth cells may play an important role in maintaining the homeostasis balance between normal microbiota, infectious pathogens and the human body, as well as regulating the qualitative composition and quantity of intestinal microorganisms [ 14 ]. Impairment of the number or function of Paneth cells is associated with a reduction in the clearance of bacterial pathogens.…”
Section: Introductionmentioning
confidence: 99%